POSSIBILITIES OF INTERVENTIONAL CORRECTION OF CRITICAL AORTIC STENOSIS: CONTEMPORARY STATE OF PROBLEM AND PERSPECTIVES - S. A. Amzaev; A. S. Sergeev; V. K. Sukhov; E. A. Shloydo; A. G. Obrezan (Креативная хирургия и онкология, 2017)
The paper studies the issues of aortic stenosis etiology and pathogenesis, clinical assessment of severity based on the distinct symptoms of decompensated aortic defect and echocardiographic measures, and modern methods of aortic stenosis correction. Valve replacement is well known as the «gold standard» in the treatment of aortic stenosis. However, the older-age-group patients with different attendant pathologies are likely to have re-operative complications during the valve replacement operation. The alternative methods of aortic stenosis treating are balloon valvuloplasty and transcatheter implantation of the aortic valve. Analyzing the experience of using the minimally invasive methods of critical aortic stenosis correction convincingly shows reduction of re-operative danger among older-age-group patients with different attendant pathologies and persuades to hospitalize old-aged comorbid patients with significant degrees of aortic valve stenosis and advanced degrees of heart failure to special medical centers. There patients can get an integrated approach to the treatment of this disease that leads to improving treatment results and favorable prognosis in this challenging group of patients.